Stephen Hawking's universe - Hawking, S. W., (Stephen W.); Martin, Philip; Langella, Frank (Hollywood, CA : Paramount, 2004)
Examines current thinking about the universe.
Seeing is believing -- The big bang -- Cosmic alchemy -- On the dark side -- Black holes and beyond -- An answer to everything.
Originally produced for television in 1997.
Cameramen, Jeff Baynes, Piers Lello ; editors, Martin Sage, Scott McEwing, Neela Sarkar ; music, Cynthia Millar.
Host, Stephen Hawking ; narrator: Frank Langella.
Not rated.
DVDs, Dolby digital.
Keywords: Hawking, S. W; Cosmology; Video recordings for hard of hearing people; Documentary films